Heparin and its contribution to the treatment of COVID-19 (Research, Society and Development, 2021)
The infection caused by SARS-CoV-2 presents changes in the coagulation processes such as venous thromboembolism (VTE) and disseminated intravascular coagulation (DIC) and it has been shown that this coagulopathy is associated by some means with the mortality. Studies suggest that these anticoagulants reduced the mortality of hospitalized patients. However, the studies for this point are not demonstrative, since they are evaluated as multiple variables and the results obtained are not the answer to experimental designs with controlled variables. In most of the cases, the obtained responses are the result of isolated cases or experimental models that do not differentiate statistical data, probably because of the differences related to the study groups. However, in models adjusted for age and sex, the reduction in mortality was statistically significant in patients who were treated with heparins, even when other variables were added to the model. In view of this, there is no consensus regarding the dose and type of anticoagulant, between different countries and entities, but what is most often cited is the use of low molecular weight heparin (LMWH) in a prophylactic dose for all hospitalized patients with the disease. The use of anticoagulants such as heparins has suggested results applicable to the treatment of coagulopathy caused by COVID-19, which makes the subject important for the centralization and analysis of the results. In order to continue with the construction of knowledge around this theme, the objective of this work was to review the use of heparins in the treatment of COVID-19.